King Thebaw and the ecological rape of Burma; the political and commercial struggle between British India and French Indo-China in Burma, 1878-1886 - Keeton, Charles Lee (Manohar Book Service, 1974)
History of Burma during the reign of King Thibaw, fl. 1875-1885.